NCLEX-PN practice questions - Rinehart Gardner, Wilda (Exam cram., 2015)
The Publisher regrets that the CD/DVD content for this title cannot be made available Online. "I studied nothing but your material for two weeks until I felt prepared to take the NCLEX ® . Studying your material gave me the confidence I needed to pass!"--Rayena Thorne, nursing student at Wallace State Covers exactly what you need to know to score higher on your NCLEX-PN ® exam. Includes more than 1,000 sample test questions to help you determine whether you're ready to take the actual exam. Our popular Cram Sheet tear card helps you remember key concepts and facts. Use our innovative Quick-Check Answer Key System "!to quickly find answers as you work your way through the questions. Score Higher on the NCLEX-PN ® Exam! NCLEX-PN ® is a registered trademark of the National Council of State Boards of Nursing, Inc. (NCSBN), which does not sponsor or endorse this product